2020
DOI: 10.1155/2020/5351318
|View full text |Cite
|
Sign up to set email alerts
|

Action Mechanism of Rosella (Hibiscus sabdariffa L.) Used to Treat Metabolic Syndrome in Elderly Women

Abstract: Objective. Rosella is a safe medicinal herb used by people in Indonesia. They believe that rosella is effective in controlling metabolic syndrome, working with antihypertension, antidiabetic, antidyslipidemia and antiobesity effects. The purpose of this study was to determine the effect of rosella in controlling metabolic syndrome through the secretion of blood nitric oxide (NO) and the cortisol pathway. Methods. This study was a quasiexperimental, pretest-posttest with control group design. The total subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 26 publications
(47 reference statements)
0
18
0
1
Order By: Relevance
“…The Harmonized criteria was most used to define MetS among participants ( n = 4), followed closely by the modified NCEP ATP III and IDF criteria with three and two studies, respectively. The study by Wahid et al [ 34 ] has reported MetS criteria other than the known definitions, while another study by Yusni et al [ 31 ] did not specify the criteria used.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Harmonized criteria was most used to define MetS among participants ( n = 4), followed closely by the modified NCEP ATP III and IDF criteria with three and two studies, respectively. The study by Wahid et al [ 34 ] has reported MetS criteria other than the known definitions, while another study by Yusni et al [ 31 ] did not specify the criteria used.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [ 31 , 33 – 35 ] reported in Southeast Asia focused on nutritional interventions within the recent ten years. Of the four, three studies [ 31 , 34 , 35 ] reported nutraceuticals or supplements.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations